Novel Pyrazole Derivatives as Anticancer and Radiosensitizing Agents - Aly, H. M.; El-Gazzar, M. G. (Arzneimittelforschung, 2012)
The present article describes the synthesis of some novel pyrrole, pyrazolo[4,3-d]oxazole, pyrrolo[2,3-b]pyridine, 1,2,3-triazole and oxoazetidin derivatives incorporating pyrazole moiety, the structures of which were confirmed by elemental analyses and spectral data. All the target compounds were subjected to in-vitro antitumor activity against liver and colon human tumor cell lines (HEPG2 and HCT), furthermore, the most potent compounds were evaluated for their ability to enhance the cell killing effect of γ-radiation (radiosensitizing evaluation). The results of in-vitro anticancer evaluation showed that compounds 3 and 16a were the most potent compounds on HEPG2 (IC50=2.6 and 4.2 µg/ml) and compounds 2 and 10 were the most potent on HCT (IC50=2.7 and 3.9 µg/ml) compared to vinblastine (IC50=4.6 on HEPG2 and 2.6 µg/ml on HCT), while, the activity of the most potent compounds increased after combination with γ-radiation and they showed no toxicity on normal hepatocytes and colon cells at their effective concentrations.
Keywords: pyrazoles; anticancer; radiosensitizing